If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -0.5(4x + -6) = 0.33(3 + -6x) + 2 Reorder the terms: -0.5(-6 + 4x) = 0.33(3 + -6x) + 2 (-6 * -0.5 + 4x * -0.5) = 0.33(3 + -6x) + 2 (3 + -2x) = 0.33(3 + -6x) + 2 3 + -2x = (3 * 0.33 + -6x * 0.33) + 2 3 + -2x = (0.99 + -1.98x) + 2 Reorder the terms: 3 + -2x = 0.99 + 2 + -1.98x Combine like terms: 0.99 + 2 = 2.99 3 + -2x = 2.99 + -1.98x Solving 3 + -2x = 2.99 + -1.98x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.98x' to each side of the equation. 3 + -2x + 1.98x = 2.99 + -1.98x + 1.98x Combine like terms: -2x + 1.98x = -0.02x 3 + -0.02x = 2.99 + -1.98x + 1.98x Combine like terms: -1.98x + 1.98x = 0.00 3 + -0.02x = 2.99 + 0.00 3 + -0.02x = 2.99 Add '-3' to each side of the equation. 3 + -3 + -0.02x = 2.99 + -3 Combine like terms: 3 + -3 = 0 0 + -0.02x = 2.99 + -3 -0.02x = 2.99 + -3 Combine like terms: 2.99 + -3 = -0.01 -0.02x = -0.01 Divide each side by '-0.02'. x = 0.5 Simplifying x = 0.5
| 8/10=c/36 | | Zw=(3+5i)(2+8i) | | h(t)=-16t^2+40x+20 | | 9x-4y+6z+23=0 | | 3(3p+7)-4(p+2)= | | 3x+3=106 | | 9x-8=104-5x | | 3-2x+5x+7= | | 0=4x^2+11x+6 | | 4-5y=16-y | | 8(x-8)+8=34-2x | | A=3(2+4i) | | a+x=13+26 | | (3-y)/5 | | 3.5-x=-2 | | 3-y/5 | | 0=x^2+10x+22 | | 4.4+1.6n=0.56 | | -8x^2+5x+18=0 | | 3(x+9)=5x+3-2x+24 | | 4(x-3)-3x+1=-13 | | -8x^2+11x+11=0 | | x-1.3= | | 3x+0y=18 | | [4-2]-10=1 | | 2(-3x-2)+4-1=15 | | 59=-3S+4 | | (8x+9)+(4x-5)= | | 90+x+67=180 | | x+(x+1)=48+(x+2) | | x(5x-36)=26 | | -2(x-2)-3(x+1)=10 |